The Factors Militating Against the Globalization of Technology Market in Nigeria: Case Study of Abuja - Akpan, Nkereuwem (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
The research attempts to ascertain the factors militating against the globalization of technology market in Nigeria using Abuja as a case study. Structured self-administered questionnaires which were distributed in both EMAB and BARNEX shopping plazas were used for Data collection. The Statistical Package for the Social Sciences (SPSS) software was utilized for data analysis. Pearson’s coefficient for correlation was used to test the relationship between the variables. The result obtained from the correlation shows that all the independent variables correlate with global market performance. The R-value, R = 0.066 indicates a low degree of correlation. The R2 value (0.047) shows that the total variation in the dependent variable can be explained by the independent variable, but not to a large degree. The study reveals some factors that militate against the globalization of technology markets in Abuja. These factors are market, entrepreneurial and network orientations, as well as network building. The results obtained show that the respondents do not have good market, entrepreneurial and network orientations as well as network building capacity. This also reflects in the R-value of 0.066 (6%) degree of correlation. From the results obtained, it is observed that the respondents have little market orientation but poor network building capacity. This research recommends that the vendors involved in computer sales and repairs should see the observed imperfection as a potential to create a better market performance by introducing new goods and services, ways of organizing markets, processes, and raw materials via organized strategies that previously had not existed.